Breaking the classroom walls: Using movies in an ESAP context - Kakoulli-Constantinou, Elis (My University, 2021)
Among the main purposes of an ESP programme is to provide learners with the knowledge of English who are expected to use the language in specific academic or professional situations. For this reason, learners should be exposed to real life language use in their field of study or professional area. This paper describes a study that will be conducted in spring 2021 in the context of an online English for Specific Academic Purposes course for 42 first year students of the Department of Commerce, Finance and Shipping at the Cyprus University of Technology. Being confined at home because of the COVID 19 pandemic, the researcher tries to find ways to immerse students in real life language use in their field of studies. To achieve that, among other things, the researcher uses movies related to the field of finance. The paper examines students’ perceptions on the use of three movies in their ESAP syllabus. Data are gathered through an online questionnaire administered to the students and from the students’ reflective journals. Drawing on previous research conducted on the use of films in ESP (Ergenekon, 2016; Kucukyilmaz, Lokmacioglu, & Balidede, 2015), it is expected that the study will yield positive results and that students will benefit in many aspects including development of vocabulary and motivation enhancement.
Keywords: G Suite for Education; reflection; ESAP; authenticity; cloud technologies